PENGARUH BUSINESS RISK, GROWTH OPPORTUNITY DAN TANGIBLE ASSETS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2019 - Rike Yolanda Panjaitan (JURNAL MANAJEMEN, 2020)
This research aims to determine and analyze the effect of business risk, tangible assets, and growth opportunity on the capital structure of mining companies listed on the Indonesia Stock Exchange for the period 2016-2019. The population of this research is 41 mining companies. The sampling technique used in this study was purposive sampling to obtain samples, so that 32 sample companies were obtained for 4 years of observation (2016-2019) with a total of 128 observations. The data analysis technique used is descriptive statistical analysis and multiple linear regression analysis. The results show that simultaneously business risk, tangible assets, and growth opportunity have the influence on capital structure, while partially tangible assets and growth opportunity had a significant influence on capital structure, while business risk had insignificant effect on capital structure in mining companies listed on the Indonesia Stock Exchange period 2016-2019.